Sagittal plane kinematics and kinetics of the pastern joint during the stance phase of the trot - Clayton, Hilary M.; Singleton, W. H.; Lanovaz, J. L.; Prades, Marta (Veterinary and Comparative Orthopaedics and Traumatology, 2002)
The objectives were to measure sagittal plane kinematics and kinetics of the forelimb pastern joint during the stance phase at the trot. Sagittal plane video (200 Hz) and force (1,000 Hz) recordings were analyzed from four trials of six sound horses trotting in hand. Kinematic and force data were used to calculate net joint moments and joint powers. The pastern joint showed maximal flexion (155.3 ± 11.0°) at 34% stance and maximal extension (190.2 ± 3.8°) at 93% stance. Energy was absorbed on the palmar aspect throughout stance, with peak energy absorption occurring in the second half of the stance. It was concluded that the primary function of the pastern joint was to act as an energy damper.
Keywords: Horse; Gait Analysis; Locomotion; Proximal Interphalangeal Joint